Comparación de dos lámparas de fotocurado de luz led convencional vs valo en la profundidad de curado en un sistema resinoso forma-ultradent (2021)
In this investigation, a comparison was made between 2 curing lamps in the depth of cure of a nanohybrid resin of enamel and dentin. The lamp that offered the greatest depth of curing of the Forma Ultradent resin was the Valo, observing a statistically significant difference of (p <0.05) giving minimum values of 1.65mm in dentin and 2.85mm in enamel; maximum values of 1.90mm dentin and 3.0 enamel compared to the conventional minimum values of 1.65mm dentin and 2.60mm enamel; maximum values of 1.74mm dentin and 2.82mm enamel.